Human Rights and Foreign Policy
XV, 208 p.
Keywords: This is an exploration of the moral and pragmatic dilemmas involved in the relationships between states in an era of change, derived from a workshop held by the Centre for International Policy Studies. The concern of those present was to examine human rights in the contemporary world.